2023
DOI: 10.1200/op.22.00702
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Trial Participants Where They Are: Decentralized Clinical Trials as a Patient-Centered Paradigm for Enhancing Accrual and Diversity in Surgical and Multidisciplinary Trials in Oncology

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…98,99 Other innovations in the structure of the clinical trials system will be necessary to truly foster diversity and representativeness, including decentralization of research to locations near patients of color. 100 In a recent analysis of accrual patterns by race for a large breast cancer cooperative group trial that oversamples Black women, we found that the most important site-level predictor of high accrual of Black patients was the proportion of Black residents in the zip code where the trial site was located. 101 Other key strategies, as outlined in a recent policy statement from the American Society of Clinical Oncology and Association of Community Cancer Centers, include education of the research workforce on equity, diversity, and inclusion issues and diversifying the workforce itself to reflect the communities in which cancer research is performed.…”
Section: Create Research Questions and Structures That Center The Nee...mentioning
confidence: 86%
See 1 more Smart Citation
“…98,99 Other innovations in the structure of the clinical trials system will be necessary to truly foster diversity and representativeness, including decentralization of research to locations near patients of color. 100 In a recent analysis of accrual patterns by race for a large breast cancer cooperative group trial that oversamples Black women, we found that the most important site-level predictor of high accrual of Black patients was the proportion of Black residents in the zip code where the trial site was located. 101 Other key strategies, as outlined in a recent policy statement from the American Society of Clinical Oncology and Association of Community Cancer Centers, include education of the research workforce on equity, diversity, and inclusion issues and diversifying the workforce itself to reflect the communities in which cancer research is performed.…”
Section: Create Research Questions and Structures That Center The Nee...mentioning
confidence: 86%
“…Two recent studies of cooperative group breast trials suggested that elimination of willing participants at the eligibility stage was not a large reason for nonparticipation, although these studies did not focus specifically on Black patients 98,99 . Other innovations in the structure of the clinical trials system will be necessary to truly foster diversity and representativeness, including decentralization of research to locations near patients of color 100 . In a recent analysis of accrual patterns by race for a large breast cancer cooperative group trial that oversamples Black women, we found that the most important site-level predictor of high accrual of Black patients was the proportion of Black residents in the zip code where the trial site was located 101 .…”
Section: Five Keys To Impactful Breast Cancer Equity Research From Ce...mentioning
confidence: 99%
“…Continuous or daily measurements also allow for a greater understanding of day‐to‐day symptom variability not captured in a pre/post design, which is particularly important for outcomes with known diurnal variability, such as lung function in asthma 27,28 . The collection of data in the home environment may represent a more accurate reflection of the patients' lived experiences than on‐site measurements, 29 aligns with a patient‐centric approach to trial design and implementation, 30 and is associated with high patient satisfaction 31 . Finally, eliminating or reducing the need for in‐clinic visits removes many barriers to trial entry, potentially increasing the rate of recruitment while improving accessibility, diversity, equity, and inclusion 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternative and creative mechanisms to collect patient-reported data should be explored, particularly methods that are accessible to patients from a variety of cultural backgrounds and levels of health literacy. 17 These considerations are critical to ensure the inclusivity of diverse patient populations, minimize undue administrative burden to patients, optimize compliance with data collection, and yield clinically meaningful results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, trial design should identify opportunities to improve data collection at multiple time points, including during the perioperative and survivorship period, to allow for improved longitudinal analysis of the cumulative impact of treatment. Alternative and creative mechanisms to collect patient-reported data should be explored, particularly methods that are accessible to patients from a variety of cultural backgrounds and levels of health literacy 17 . These considerations are critical to ensure the inclusivity of diverse patient populations, minimize undue administrative burden to patients, optimize compliance with data collection, and yield clinically meaningful results.…”
Section: Discussionmentioning
confidence: 99%